The Bernhardt of Scandinavia: Betty Nansen’s Modern Breakthrough - Adriaensens, Vito (Nineteenth Century Theatre and Film, 2018)
The cinema of the 1910s witnessed the birth of the film star, modelled after theatrical strategies that were spearheaded by actresses of international renown such as Sarah Bernhardt. She can be seen to have given birth to the notion of ‘famous players in famous plays’ in 1912, though in Denmark, the influential Nordisk Films Kompagni had already invested more extensively in marketing the appeal of theatrical stars that crossed over into the realm of film by this time. I will trace how Nordic drama was marketed internationally by analysing the trajectory of one of the most important, yet undervalued, actresses of the time, Betty Nansen (1873–1943) – also known as the Bernhardt of Scandinavia. Nansen was the model for the new ‘post-Ibsen’ female in Scandinavian society, both on and off the stage, and additionally a key example of how theatre and film uniquely managed to bridge the gap in Denmark. Betty Nansen’s stage and screen work reinforced each other, from the Danish Royal Theatre to the American Fox Film Corporation, and to managing her own theatre in Copenhagen, the still extant Betty Nansen Teatret.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8xNzQ4MzcyNzE4Nzk0MzYw